Biogas Stove Design and Test for Household Scale - Hurip Jayadi; Sujangi Sujangi; Beny Suyanto (Alliance oh Health Activists (AloHA), 2021)
This research is an increase in the performance of biogas stoves from cow dung, for household needs. This type of research is experimental, with the independent variables being a blower with a power of 2.5 watts, two variations of burner holes 4.1 mm and 4.5 mm, and 10 times replication. The dependent variables are stove power, stove efficiency, length of time required for testing and heat and efficiency level. The specifications of the biogas stove are made of zinc (height: 9 cm, width: 38 cm and length: 70 cm), with two stoves, the gas distribution line is made of brass pipe with a diameter of 5 mm, the fire pit size (burner) is 4.1 mm and 4.5 mm, blower: 2.5 watts, factory valve opening max 5 mm, refill gas lighter system shaped like a gun that is separated from the stove, biogas fuel is cow dung. The results of the Water boilling test are that the power of the stove with a diameter of 4.1 mm and a blower of 2.5 watts is 0.904352 KW and the efficiency is 55.748%; while for a fire pit with a diameter of 4.5 mm and a blower of 2.5 watts it is 1.185 KW and the efficiency is 51.838%. Furthermore, it is concluded that smaller burner holes are more efficient. Larger burners will be more wasteful, but can save time. Keywords: biogas stove; digesters; blowers; burner